The effect of WWTP products amendments on Phaseolus vulgaris rhizosphere and its ability to inactivate clarithromycin - Kotrbová, Lucie; Grabicová, Kateřina; Švecová, Helena; Staňová, Andrea Vojs; Petrlíková, Martina; Grabic, Roman; Kodešová, Radka; Chroňáková, Alica (Scientific reports, 2025)
With increasing efforts to reuse wastewater treatment plant (WWTP) products in agriculture, assessing their impact on soil-plant systems is crucial, while the effects of accompanying antibiotic residues on soil microbial communities have not yet been adequately studied. This study focuses on clarithromycin (CLR), highly present in wastewater, and investigates the CLR-degradation potential of plant-associated microorganisms. Phaseolus vulgaris plants were grown in raised beds filled with Haplic Cambisol and amended with or without WWTP products (treated wastewater, biosolid, or composted biosolid), as a source of CLR residues. The rhizosphere microbiomes after biosolid amendments was significantly enriched by Pseudomonadaceae as assessed by 16S rRNA metagenomics and cultures enriched by CLR revealed dominance of Proteobacteria. However, no degradation of CLR by microbial consortia or enrichment cultures was observed, suggesting the multiplication of CLR-resistant bacteria with other resistance mechanisms. Cultivation-based approach combined with antibiotic modulation assays and subsequent LC-MS analysis confirmed the complete CLR removal by seven phylogenetic groups of actinomycetes in vitro. The proportion of isolates indicated that the rhizosphere is a natural reservoir for CLR-inactivating microorganisms; however, the amendment of soils with WWTP products can significantly increase their abundance and diversity.
Keywords: fylogeneze; Streptomyces; RNA, Ribosomal, 16S; Biodegradation; mikrobiota; Micropollutants; Phylogeny; antibakteriální látky; fazol; odpadní voda; Soil Microbiology; klarithromycin; Microbiota; rhizosféra; Antimicrobial resistance; Anti-Bacterial Agents; Clarithromycin; Phaseolus; Rhizosphere; Soil microbiome; RNA ribozomální 16S; půdní mikrobiologie; Macrolides; Wastewater